Some aspects of ensuring the rights of children to education in case of a pandemic - Dusmukhamedova, Nargiza (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article discusses some topical issues of ensuring the right of children to education in a pandemic. The transition to a distance and online system of continuing general secondary, secondary special and higher education in Uzbekistan, the positive and problematic aspects of this system, the results of studying the experience of international organizations and foreign countries in this field are discussed